Di‐ and Triphosphate Recognition and Sensing with Mono‐ and Dinuclear Fluorescent Zinc(II) Complexes: Clues for the Design of Selective Chemosensors for Anions in Aqueous Media. Issue 42 (30th August 2016) - Bartoli, Francesco; Bencini, Andrea; Garau, Alessandra; Giorgi, Claudia; Lippolis, Vito; Lunghi, Alessandro; Totti, Federico; Valtancoli, Barbara
Abstract: The synthesis of a new ligand (L1) containing two 1, 4, 7‐triazacyclononane ([9]aneN3 ) moieties linked by a 4, 5‐dimethylenacridine unit is reported. The binding and fluorescence sensing properties toward Cu 2+, Zn 2+, Cd 2+, and Pb 2+ of L1 and receptor L2, composed of two [9]aneN3 macrocycles bridged by a 6, 6′′‐dimethylen‐2, 2′:6′, 2′′‐terpyridine unit, have been studied by coupling potentiometric, UV/Vis absorption, and emission measurements in aqueous media. Both receptors can selectively detect Zn 2+ thanks to fluorescence emission enhancement upon metal binding. The analysis of the binding and sensing properties of the Zn 2+ complexes toward inorganic anions revealed that the dinuclear Zn 2+ complex of L1 selectively binds and senses the triphosphate anion (TP), whereas the mononuclear Zn 2+ complex of L2 displays selective recognition of diphosphate (DP). Binding of TP or DP induces emission quenching of the Zn 2+ complexes with L1 and L2, respectively. These results are exploited to discuss the role played by pH, number of coordinated metal cations, and binding ability of the bridging units in metal and/or anion coordination and sensing. Abstract : Phosphate recognition : Zn 2+ complexes with L1 and L2 are able to selectively bind and sense diphosphate and triphosphate anions, respectively, through an OFF–ON–OFF switching of their emission upon subsequent metal and anion binding. They represent unique cases of optical switches whose performances are simultaneously controlled by multiple factors, including pH, number and type of coordinated metals, flexibility and binding ability of the spacer (see figure).